Sound absorption characteristics of the natural fibrous material from coconut coir, oil palm fruit bunches, and pineapple leaf. (August 2019) - Rusli, M; Irsyad, M; Dahlan, H; Gusriwandi,; Bur, M
Abstract: In this paper sound absorption characteristics of three kinds of natural fiber composite is evaluated. The fibers are made from coconut coir, oil palm fiber from empty fruit bunches, and pineapple leaf. The sound absorption coefficient is evaluated using a specimen thickness of 10 mm and 20 mm and two variants of fiber density. A simple impedance tube with two microphones is used in the measurement. The sound absorption coefficient is calculated by the transfer function of the two microphones within 200 Hz to 3000 Hz frequency range. It is revealed that three types of fibers can reduce reflected sound in relatively higher frequency. Denser and thicker of a fibrous material increases the sound absorption of the material and shifts the peak of the absorption coefficient into a lower frequency. Furthermore, pineapple leaf fiber has the highest sound absorption coefficient among others type of fibers. Smaller and uniform fiber diameter has a significant role to absorb sound energy in pineapple fiber. Whereas, coconut coir and palm empty fruit bunches fiber have larger, various and random fiber diameters, that could make the sound absorption coefficient become lower, especially within the frequency range of measurement.